2019
DOI: 10.3390/en12224289
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Interrelation between Temperature Distribution and Dry Band on Wet Contaminated Insulators

Abstract: In this paper, the interrelation between temperature distribution and dry band on wet contaminated insulators is studied by theoretical analysis, numerical simulation, and a high-voltage artificial contamination experiment. The influences of the composition of the contaminant and the relative humidity of the environment on the moisture absorption of the contamination layer are studied. It is indicated that the critical relative humidity (CRH) of the soluble mixture in the contamination layer decreases with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
(12 reference statements)
1
3
0
Order By: Relevance
“…This conclusion appears to be justified by the results in Figure 11, in which the maximum average temperature reached at the middle of the dry band was highest for Plexiglas (99 • C), followed by RTV (82 • C) and glass (34 • C). The value obtained for the glass substrate seems to be in accordance with experimental measurements performed on a real wet contaminated ceramic insulator [42]. These observations suggested that the higher thermal conductivity of the glass substrate decreased the temperature at the surface of the pollution layer by allowing for better thermal conduction through the sample thickness.…”
Section: Influence Of Parameters On Dry Band Formationsupporting
confidence: 87%
“…This conclusion appears to be justified by the results in Figure 11, in which the maximum average temperature reached at the middle of the dry band was highest for Plexiglas (99 • C), followed by RTV (82 • C) and glass (34 • C). The value obtained for the glass substrate seems to be in accordance with experimental measurements performed on a real wet contaminated ceramic insulator [42]. These observations suggested that the higher thermal conductivity of the glass substrate decreased the temperature at the surface of the pollution layer by allowing for better thermal conduction through the sample thickness.…”
Section: Influence Of Parameters On Dry Band Formationsupporting
confidence: 87%
“…The results showed that the float potential metal has a strong distortion effect on the current density, and it is easy to form a dry band through the contaminated layer, which triggers the arc discharge. Several scholars have carried out experimental and simulation studies on the dry band discharge on the insulator surface [14][15][16][17]. However, there are connections between the composite rod and metal/composite plate in the tower, which may also lead to electric field distortion.…”
Section: Introductionmentioning
confidence: 99%
“…The main sensing elements are the instrument transformers (ITs), which measure voltages and currents, scaling them to suitable values for the acquisition systems. Of course, environmental quantities can be measured as well (such as in [4][5][6][7] for cables, and in [8][9][10] for insulators, etc.) but out of the scope of this paper.…”
Section: Introductionmentioning
confidence: 99%